Cultural Rights and Justice Sustainable Development, the Arts and the Body - Clammer, John.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book provides an innovative contribution to the emerging field of culture and development through the lens of cultural rights, arguing in favour of a fruitful dialogue between human rights, development studies, critical cultural studies, and concerns about the protection and preservation of cultural diversity. It breaks with established approaches by introducing the themes of aesthetics, embodiment, narrative and peace studies into the field of culture and development, and in doing so, proposes both an expanded conception of cultural rights and a holistic vision of development that not only includes these elements in a central way, but which argues that genuine sustainability must include the cultural dimension, including the notion of cultural justice as recognition, protection and respect extended to the many expressions of human imagination in this world.
Culture, Development and Cultural Rights -- Cultural Rights, Development and Sustainability -- Cultural Rights, Business and the Ethics of Development: Bringing Social Ethics Back In -- Is Multiculturalism the Answer? Global Ethics and the Dialectic of the Universal and the Particular -- Globalization and the Transnationalisation of Culture: Implications for Cultural Rights -- Visual Justice: The Right to Beauty? -- The Right to Peace? Cultural Values, Peace and Conflict Resolution -- Embodying Rights -- Transformative Narratives of Peace and Justice -- Advancing Cultural Rights: Holistic Development and Sustainable Futures.
Keywords: Human rights; Culture; Economic development; Developmental psychology; Human Rights; Global and International Culture; Sociology of Culture; Development Studies; Developmental Psychology